2015
DOI: 10.1007/s10278-014-9756-2
|View full text |Cite
|
Sign up to set email alerts
|

“Evaluation of a Very Low-Cost and Simple Teleradiology Technique”

Abstract: This paper describes and analyzes a proposed solution of fundamental limitative factor of teleradiology to overcome the teleradiology usages problems in underdeveloped and developing countries. The goal is to achieve a very simple and cost-efficient way to take advantage of teleradiology in anywhere even in remote and rural areas. To meet the goal of this study, the following methodology which is consists of two main procedures was done: (1) Using a digital camera in order to provide a digital image from radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Moreover, the use of teleophthalmology and modern information technology tools and protocols has been suggested [ 21 ]. Although several studies have been conducted regarding the application of telemedicine technology in the country [ 22 - 25 ], it was the first time that a teleophthalmology system was developed using the method of store-and-forward. It is expected that the eye care services and saving costs can be gained directly or indirectly by using the system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of teleophthalmology and modern information technology tools and protocols has been suggested [ 21 ]. Although several studies have been conducted regarding the application of telemedicine technology in the country [ 22 - 25 ], it was the first time that a teleophthalmology system was developed using the method of store-and-forward. It is expected that the eye care services and saving costs can be gained directly or indirectly by using the system.…”
Section: Introductionmentioning
confidence: 99%
“…Teledermatology is widely used for the purposes of treating skin conditions, due to its ability to meet the needs of a field reliant on visual information. 6 Some telemedicine and teledermatology studies reviewed showed good diagnostic concordance [7][8][9][10] and reductions in delay of treatment. 11 Individuals using SAF systems generally had positive perceptions such as confidence in using it, and positive opinions regarding quality of care, ability to improve communication, patient satisfaction and building up a repository of information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of the literature reveals that several specialized medical areas, including dermatology, ophthalmology, radiology, and nursing have benefitted from image transmission via mobile devices [1,2,[14][15][16][17]. It is also evident that mobile phone technology has been used to transmit digital images from neurosurgical patients to health professionals, resulting in informed decisions being made about patient transference to specialized facilities [18].…”
Section: Literature Reviewmentioning
confidence: 99%